1976
DOI: 10.1111/j.1365-2427.1976.tb01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Body length, size of resting eggs and identification of the ephippia of Ceriodaphnia megalops and Ceriodaphnia pulchella

Abstract: The ephippia of Ceriodaphnia megalops and Ceriodaphnia pulchella are described. Their ephippia may be identified by their size and shape, supplemented by measurement of the length of the resting egg. The ephippia are shed free in the water and float by means of a special area of gas-filled tissue. Each ephippium contained one ellipsoid resting egg. The length, width and shape of the resting eggs of both species were investigated, and comparisons made with published data of their parthenogenetic eggs. For both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…3). Few cases of successful discrimination of Ceriodaphnia species using ephippia were made previously (Bottrell, Newsome, 1976;Berner, 1985), but our recent investigation confirmed that at least main species groups of Ceriodaphnia could be identified based on ephippial morphology under both optical and scanning electron microscope .…”
Section: Resultsmentioning
confidence: 54%
“…3). Few cases of successful discrimination of Ceriodaphnia species using ephippia were made previously (Bottrell, Newsome, 1976;Berner, 1985), but our recent investigation confirmed that at least main species groups of Ceriodaphnia could be identified based on ephippial morphology under both optical and scanning electron microscope .…”
Section: Resultsmentioning
confidence: 54%